Pulmonary Arteriovenous Malformations (PAVMs) and Pregnancy: A Rare Case of Hemothorax and Review of the Literature - Federica Di Guardo; Viviana Lo Presti; Giuliana Costanzo; Elisa Zambrotta; Luisa Maria Di Gregorio; Antonio Basile; Marco Palumbo (Case Reports in Obstetrics and Gynecology)
Pulmonary arteriovenous malformations (PAVMs) are anatomical abnormalities consisting in a direct connection between pulmonary arteries and veins. Most of PAVMs are related to Hereditary Hemorrhagic Teleangiectasia, whereas only 10 to 20% are isolated sporadic cases. PAVMs tend to increase in size naturally; however, several factors can influence their growth such as pulmonary arterial hypertension, puberty, and pregnancy. Clinical manifestations are related to the right-to-left shunting and include dyspnoea, hypoxia, and pulmonary hypertension. The presence of PAVMs during pregnancy is associated with an increased risk of complications such as their rupture, haemothorax, and hypovolemic shock. The treatment reserved to PAVMs was the surgical resection of the lung lobe involving the malformation. Due to the worldwide acceptance of endovascular technique, the transcatheter embolization (TCE) is today considered as the mainstay of treatment. Recent studies reported the safeness of the TCE during pregnancy if performed by an experienced radiologist, at second or third trimesters when radiation exposure is believed to have minimal effect on the foetus. However, although the TCE during pregnancy represents an option, the treatment prior to pregnancy has to be considered the auspicial solution. Our study reports the case of a dyspnoeic pregnant woman with unknown pAVM causing hemothorax and simultaneously treated for pAVM reparation, left lower lobe resection, and hysterectomy. Postoperative treatment of embolization was performed to definitively close the pAVM.